Elements, resources and capacities of agricultural production units: from a thoughtful analytical approach (2019)
The article discusses the elements, resources and capacities of agricultural production units. Based on the reflexive analytical approach of classical and current theoretical benchmarks. A Subjective interpretation is proposed as a central point to provide tools that contribute to the identification and configuration of elements of a system, resources with what works and organizational capabilities, leading to competitive advantages and interdependence relationships of companies. The findings show that agricultural production units will need to implement strategies to achieve levels of growth that help overcome gaps and problems of hunger and poverty in the world.